Humerus Rotation Has a Negligible Effect on Baumann Angle in a Wide Range of Rotational Positions. Issue 9 (October 2020) - Segal, David; Emery, Kathleen; Zeitlinger, Lauren; Rosenbaum, Joseph A.; Little, Kevin J.
Abstract : Background: Rotation of the humerus out of the coronal plane is presumed to alter the Baumann angle (BA) value. Identifying the rotational limits of the humerus at which the BA can be accurately and reliably measured will circumvent repeated radiographs and unnecessary exposure to radiation, may improve patient comfort, and save time and medical resources. Methods: A retrospective chart review was performed to identify patients under the age of 18 who underwent an elbow computed tomography (CT) scan without any humeral pathology and with an open distal humeral physis. For each patient, a 3-dimensional (3D) computerized model was generated with 30% transparency to mimic a plain radiograph. These models were rotated in 10-degree increments and the BA was measured on each position. In addition, the measurements were taken on an anteroposterior radiograph for each patient. Analysis of variance and the Pearson tests were performed to locate differences and define associations. Results: Fifteen 3D CT reconstructions were generated from 14 patients. The mean BA on the neutral position was found to be 72.2±3 degrees, which correlated with the 70.6±5.91 degrees measurement obtained on radiographs. The most extreme rotational positions on which the BA values were consistent with the neutral position values were +40 external rotation (70.97±7.01 degrees, P =1) and −70 degrees internal rotation (68.4±7.47 degrees, P =0.14). A negative correlation was found between the BA values and the extent at which the humerus was rotated from the neutral position. The variability of the BA between patients, implied by the SD of measurements on each position increased with increasing rotation from the neutral position ( r =1, P <0.05). Conclusions: On the basis of 3D CT images, the BA is the most accurate when the arm is positioned at an exact anteroposterior position. It is reliable to measure the BA when the humerus is rotated no more than +40 degrees external rotation to −70 degrees internal rotation. This range of rotation can act as an "accurate zone" and help avoiding multiple radiographs. Level of Evidence: Level III.